UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DENGAN MENGGUNAKAN PROBLEM-BASED LEARNING KELAS X SMA KARYA PEMBANGUNAN CICALENGKA - Yayang Anggraeni; Devi Nurul Yuspriyati (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This research is motivated by the low ability of students to understand basic concepts and students' interest in learning mathematics. The purpose of this study was to determine the improvement of student learning outcomes through the use of Problem-Based Learning in class X mathematics subjects. The research method used was qualitative and quantitative data analysis, with the research subjects of all 34 students of class X. Based on the processing and results of data analysis, the application of the Problem-Based Learning model in mathematics learning has increased after the actions of cycle I, II, and cycle III were held. Student learning outcomes in the first cycle have an average grade of 73.5%, student learning outcomes in the second cycle have slightly increased, namely the average grade of 81.4% and classical absorption of 73.5%, then proceed to the cycle III and experienced an even better improvement, with an average grade of 83.5% and classical absorption of 88.2%. The conclusion of this research is that learning mathematics using Problem-Based Learning can improve the learning outcomes of class X students at SMA Karya Pembangunan Cicalengka.